PENDUGAAN PEWARISAN SIFAT KETAHANAN KENAF TERHADAP NEMATODA PURU AKAR (Meliodogyne incognita) - Parnidi Parnidi; Aditya Aji Noftara; Mala Murianingrum; Taufiq Hidayat RS; Marjani Marjani (Jurnal Penelitian Pendidikan IPA, 2022)
Root puru nematodes (Meloidogyne spp.) on kenaf plants are known as one of the harmful plant-disturbing organisms. NPA infection in roots causes plants to grow stunted and production potential decreases. The inheritance of kenaf resistance to NPA M. incognita was carried out using a sixpopulation approach (P1, P2, F1, F2 BC1P1 and BC1P2). The genotype (Kenafindo Agribun 2 = Kin2) which was highly susceptible to NPA M. incognita was used as the female parent and the tolerant genotype (Karangploso 15 = KR15) as the male parent. The nature of kenaf resistance to NPA M. incognita was based on the variable number of shells, reproductive factors, number of 2nd instar juveniles, number of egg masses and number of eggs per egg mass. Based on the results of the study showed that the resistance of kenaf to NPA M. incognita showed that it was not influenced by female parents. The number of resistance genes is controlled by one gene. The character of kenaf resistance to NPA M. incognita was controlled by a partially positive dominant gene. The action of genes controlling resistance to NPA M. incognita was additive-dominant. The heritability value in the broad sense and the heritability value in the narrow sense for all variables of kenaf resistance to NPA M. incognita were high